Land‐use history as a guide for forest conservation and management. Issue 1 (23rd August 2017) - Whitlock, Cathy; Colombaroli, Daniele; Conedera, Marco; Tinner, Willy
Abstract: Conservation efforts to protect forested landscapes are challenged by climate projections that suggest substantial restructuring of vegetation and disturbance regimes in the future. In this regard, paleoecological records that describe ecosystem responses to past variations in climate, fire, and human activity offer critical information for assessing present landscape conditions and future landscape vulnerability. We illustrate this point drawing on 8 sites in the northwestern United States, New Zealand, Patagonia, and central and southern Europe that have undergone different levels of climate and land‐use change. These sites fall along a gradient of landscape conditions that range from nearly pristine (i.e., vegetation and disturbance shaped primarily by past climate and biophysical constraints) to highly altered (i.e., landscapes that have been intensely modified by past human activity). Position on this gradient has implications for understanding the role of natural and anthropogenic disturbance in shaping ecosystem dynamics and assessments of present biodiversity, including recognizing missing or overrepresented species. Dramatic vegetation reorganization occurred at all study sites as a result of postglacial climate variations. In nearly pristine landscapes, such as those in Yellowstone National Park, climate has remained the primary driver of ecosystem change up to the present day. In Europe, natural vegetation–climate–fire linkages were broken 6000–8000 years ago with the onset of Neolithic farming, and in New Zealand, natural linkages were first lost about 700 years ago with arrival of the Maori people. In the U.S. Northwest and Patagonia, the greatest landscape alteration occurred in the last 150 years with Euro‐American settlement. Paleoecology is sometimes the best and only tool for evaluating the degree of landscape alteration and the extent to which landscapes retain natural components. Information on landscape‐level history thus helps assess current ecological change, clarify management objectives, and define conservation strategies that seek to protect both natural and cultural elements.